2001
DOI: 10.1093/toxsci/60.2.252
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pregnancy on Renal Clearance of Boron in Humans: A Study Based on Normal Dietary Intake of Boron

Abstract: Boron occurs most frequently in nature as borates and boric acid, never as the free element. Its largest uses are in glass, detergents, and agriculture. Essential for higher plants, there is growing evidence for essentiality in vertebrates. Humans consume daily about a milligram of boron, mostly from fruit and vegetables. At high doses, boron is a developmental and reproductive toxin in animals. Pregnant rats were the most sensitive. An oral NOAEL of 9.6 mg B/kg/day was established for developmental toxicity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…To our knowledge, this is the first human study reporting on the postprandial increase in plasma boron following consumption of a boron supplement alone. Fasting plasma boron concentrations were in keeping with results of previous studies which have reported on plasma boron concentrations (Ferrando & Green, 1993;Green & Ferrando, 1994;Vanhoe et al, 1995;Pahl et al, 2001). The richest food sources of boron are fruit, vegetables, pulses, legumes and nuts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To our knowledge, this is the first human study reporting on the postprandial increase in plasma boron following consumption of a boron supplement alone. Fasting plasma boron concentrations were in keeping with results of previous studies which have reported on plasma boron concentrations (Ferrando & Green, 1993;Green & Ferrando, 1994;Vanhoe et al, 1995;Pahl et al, 2001). The richest food sources of boron are fruit, vegetables, pulses, legumes and nuts.…”
Section: Discussionsupporting
confidence: 89%
“…Boron concentration in plasma and urine was determined by West Coast Analytical Service Inc. (Santa Fe Springs, CA, USA) using inductively coupled plasma mass spectrometry (ICP-MS) as described in Pahl et al (2001). The detection limit of the assay for boron was 0.01 mg=g for the plasma samples and 0.10 mg=l for the urine samples.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…Rai et al (1986) concluded that because most environmentally relevant boron minerals are highly soluble in water, it is unlikely that mineral equilibria will control the fate of boron in water. Boron was found to not be significantly removed during the conventional treatment of waste water (Matthijs et al 1999;Pahl et al 2001;Waggott 1969). Boron may, however, be co-precipitated with aluminum, silicon, or iron to form hydroxyborate compounds on the surfaces of minerals (Biggar and Fireman 1960).…”
Section: Transport and Partitioningmentioning
confidence: 96%
“…Boric acid was detected in urine of patients 23 days after a single ingestion (Wong et al 1964). Renal clearance of dietary boron from fifteen pregnant women was calculated to be 1.02 mL/minute/kg, or 66.1 mL/minute (Pahl et al 2001). …”
Section: Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation